2013
DOI: 10.1039/c2cs35441a
|View full text |Cite
|
Sign up to set email alerts
|

Methods to produce B–C, B–P, B–N and B–S bonds in boron clusters

Abstract: Boranes, heteroboranes and metallacarboranes, all named as boron clusters, offer an alternative to typical organic molecules or organic molecular materials. Carbon and boron share the important property of self-catenation thus these elements can produce individually large and sophisticated molecules. Boron clusters and organic molecules display electronic, physical, chemical and geometrical characteristics manifestly different. These differences highlight the complementarity of organic molecules and boron clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
132
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 295 publications
(133 citation statements)
references
References 78 publications
1
132
0
Order By: Relevance
“…The present work demonstrates that 1,3-dehydro-o-carborane is a useful synthon for simultaneous C,B functionalization of o-carboranes. [18] Experimental Section Typical procedure: Benzene (2 a; 1 mL) was added to a mixture of 1 (51.6 mg, 0.2 mmol) and LDA (0.2 mmol) under an atmosphere of dry argon. The resulting mixture was stirred at room temperature for 10 min and quenched by wet n-hexane.…”
mentioning
confidence: 99%
“…The present work demonstrates that 1,3-dehydro-o-carborane is a useful synthon for simultaneous C,B functionalization of o-carboranes. [18] Experimental Section Typical procedure: Benzene (2 a; 1 mL) was added to a mixture of 1 (51.6 mg, 0.2 mmol) and LDA (0.2 mmol) under an atmosphere of dry argon. The resulting mixture was stirred at room temperature for 10 min and quenched by wet n-hexane.…”
mentioning
confidence: 99%
“…[4] Earlier we and others had demonstrated that starting from monoiodinated metallacarboranes, [4,16] alkyl derivatives can be produced by am odification of the Kumada reaction. In Scheme 1, the syntheses of [3,3'-Co(9,12-I 2 -1,2-closo-C 2 B 9 H 9 ) 2 ] À (I 4 - [1] À )a nd [3,3'-Co(9,12-(Me) 2 -1,2-closo-C 2 B 9 H 9 ) 2 ] À ((Me) 4 - [1] À ), are shown. Similar procedures have been utilized to produce other I-or Me-polysubstituted [1] À derivatives studied in this work.…”
Section: Resultsmentioning
confidence: 99%
“…[4] The central core of this anion, "Co(C 2 B 3 ) 2 ", is very similar to the core of ferrocene, "Fe(C 5 ) 2 ", thus they bear resemblances in some respects, for example, the reversible electrochemistry [5] and the high chemical and thermal stability. [6] However,t hey are different in other respects, such an enhanced protection of the cobalt in [1] À by ac anopy of boron hydrogen atoms [7] and properties derived from the six additional atoms placed in two furtherp lanes from the core (B 5 plane and B 1 ).…”
Section: Introductionmentioning
confidence: 98%
“…The presentw ork also demonstrates that 1,3-dehydroo-carborane is au seful synthon for selectivec age B-functionalization of o-carboranes. [19] The newly prepared carboranyl-alkenes and -allenes may serve as useful startingm aterials for further functionalization. HNMR spectroscopy and then subjected to flash column chromatography on silica gel (230-400 mesh) using n-hexane as eluent to give desired product 5a as colorless crystals (45.3 mg, 92 %).…”
mentioning
confidence: 99%